2001
DOI: 10.4000/bifea.7349
|View full text |Cite
|
Sign up to set email alerts
|

¿Shashal o no shashal? Esa es la cuestiónEtnoarqueología cerámica en la zona de Huari, Ancash

Abstract: Ceramic production in the Huari region, Ancash, is characterized by the use of ground slate, a temper called shashal, mixed to a yellow clay. Two of the three villages producing around Huari exchange their materials. Further north, in the San Luis-Chacas region, other villages use also shashal. What are the compositional differences of this material? How can we distinguish one producing village from the other? What is shashal? The content of carbon varies from one mine and one region to the other, and determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
12

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 10 publications
0
2
0
12
Order By: Relevance
“…Brevemente esbozada, la historia de Conchucos central sigue los desarrollos observados en otras partes de la sierra de Áncash después del declive de Chavín, pero con menos fuerza. La tradición tecnológica cerámica cambió después de Chavín con el uso de otras materias primas (Druc, 2001), registros decorativos y formas (Lau, 2004: 189;2013: 30-32). En el Intermedio Temprano, la cultura Recuay prevalece en el Callejón de Huaylas, con su cerámica fina de caolín y su arte lítico e impacta las regiones adyacentes, como en Conchucos, en la cuenca y valle del Yanamayo (Lau, 2002;2010;Wegner, 2000;2011).…”
Section: Antecedentesunclassified
See 2 more Smart Citations
“…Brevemente esbozada, la historia de Conchucos central sigue los desarrollos observados en otras partes de la sierra de Áncash después del declive de Chavín, pero con menos fuerza. La tradición tecnológica cerámica cambió después de Chavín con el uso de otras materias primas (Druc, 2001), registros decorativos y formas (Lau, 2004: 189;2013: 30-32). En el Intermedio Temprano, la cultura Recuay prevalece en el Callejón de Huaylas, con su cerámica fina de caolín y su arte lítico e impacta las regiones adyacentes, como en Conchucos, en la cuenca y valle del Yanamayo (Lau, 2002;2010;Wegner, 2000;2011).…”
Section: Antecedentesunclassified
“…Estas informaciones junto con el presente análisis permiten proponer unas hipótesis de producción cerámica para este período en la región de Huari. En la zona de Huari, también se llevó a cabo un análisis de pasta de carácter etnohistórico y etnoarqueológico (Druc, 2001;2005) que permitió distinguir dos tradiciones cerámicas antiguas en relación con las parcialidades del grupo preincaico huari: Ichochuari y Allaucahuari (Druc, 2009). Otro estudio comparativo de interés es el de Rafael Vega Centeno et al (2014) sobre la cerámica del Intermedio Tardío de Huacramarca, un sitio de altura cerca de Chacas, en la cuenca del río Yanamayo.…”
Section: Antecedentesunclassified
See 1 more Smart Citation
“…These broad regional technical traditions are complemented by community level specializations where several pottery making families produce similar forms and styles (Sillar 2000a), with a further dynamic as individual potters adapt and borrow techniques (Sillar 1997). There is a growing interest in reporting transcripts of local testimonies, such as Druc's (2001) review of potter's discussions of shashal, a raw material used in Ancash and La Libertad. The inclusion of the potter's, or the users of pottery, voices and reproduction of complete interviews (e.g.…”
Section: Production Techniques and The Organisation Of Craft Productionmentioning
confidence: 99%
“…These are themes that Arnold has addressed more fully in his Maya research where he has shown that the time commitment potters make to their craft varies in relation to other social and economic commitments as well as changes in market demand, suggesting that measures of output, technological investment and use of space are more applicable ways of assessing the degree of craft specialisation (Arnold 2015, 285-6). Arnold (1972) Druc's ethnographic work in Ancash, Conchucos (Druc 1996(Druc , 2001(Druc , 2005 and Cajamarca (Druc 2011) has also largely focused on describing modern potters collection and processing of raw materials which she combined with detailed laboratory analysis (Druc and Chávez 2014). This has contributed to her research into the distribution of archaeological ceramics (Druc 1998) and informed her reference books and identification manuals for the description and interpretation of pottery fabrics.…”
Section: Production Techniques and The Organisation Of Craft Productionmentioning
confidence: 99%